Macroeconomic and stock market interactions with endogenous aggregate sentiment dynamics - Peter Flaschel; Matthieu Charpe; Giorgos Galanis; Christian R. Proa\~no; Roberto Veneziani (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2017)
This paper studies the implications of heterogeneous capital gain expectations on output andasset prices. We consider a disequilibrium macroeconomic model where agents' expectations on future capital gains affect aggregate demand. Agents' beliefs take two forms - fundamentalist and chartist - and the relative weight of the two types of agents is endogenously determined. We show that there are two sources of instability arising from the interaction of the financial with the real part of the economy, and from the heterogeneous opinion dynamics. Two main conclusions are derived. On the one hand, perhaps surprisingly, the non-linearity embedded in the opinion dynamics far from the steady state can play a stabilizing role by preventing the economy from moving towards an explosive path. On the other hand, however, real-financial interactions and sentiment dynamics do amplify exogenous shocks and tend to generate persistent fluctuations and the associated welfare losses. We consider alternative policies to mitigate these effects. – – Dieses Papier untersucht die Implikationen heterogener Kapitalgewinnerwartungen bzgl. Output und Aktienpreise. Wir betrachten dabei ein Ungleichgewichts-Makromodell, in dem die Erwartungen der Agenten bzgl. zukünftiger Kapitalgewinne die aggregierte Nachfrage beeinflussen. Die Erwartungen der Agenten treten auf zweierlei Weise - fundamentalistisch und chartistisch - in Erscheinung, und die relative Gewichtung der beiden Agententypen ist endogen bestimmt. Wir zeigen insbesondere, dass zwei Quellen von Instabilität von der Interaktion des Finanz- mit dem realen Wirtschaftssektor, und von der heterogenen Stimmungsdynamiken entstehen können. Wir erreichen zwei Hauptschlußfolgerungen. Auf der einen Seite, kann die in der Stimmungsdynamik eingebettete Nichtlinearität weit vom Gleichgewichtszustand eine stabilisierende Rolle spielen, indem sie verhindert, dass sich die Wirtschaft auf einen explosiven Pfad hinzubewegt. Andererseits verstärken reale Finanzinteraktionen und Stimmungsdynamiken exogene Schocks und neigen dazu, anhaltende Schwankungen und damit verbundene Wohlfahrtsverluste zu erzeugen. Wir betrachten alternative Politikmaßnahmen, um diese Effekte zu mildern.
urn:nbn:de:101:1-2017112013867
Keywords: E12; E24; E32; E44; 330; Real-financial interactions; heterogeneous expectations; aggregate sentiment dynamics; macro-financial instability